The preservation of life as a duty and a right - Basile, Giuseppe (Medicina Historica, 2022)
With considerable insight for the time, 65 years ago Pope Pius XII outlined a proposal of evaluation criteria based on the distinction between ordinary means of care, i.e. those who do not entail unreasonable sacrifices which would be unacceptable for most professionals and patients, and extraordinary care procedures which, although not mandatory, could be used if one had the intellectual, moral, spiritual, scientific and organizational awareness, capabilities and strength to put them in place. The Pope thus addressed the extremely complex set of bioethical issues stemming from the implementation of resuscitation procedures for those who have no hope to recover. The core belief was that every decision based on free consent to treatment should be made within the framework of an underlying and essential linkage between the rights and duties of doctors and those of patients. The identification of the patient as the ultimate decision-maker, when it comes to their health and the therapeutic interventions to be administered, has been the result of a cultural and legal evolution, in keeping with the principle of consent enshrined in art. 32 of the Italian Constitution, according to which “no one can be obliged to undergo any given health treatment except by law. The law cannot therefore exceed the limits imposed by “respect for all human beings”. On March 10th , 2022, the Italian Chamber of Deputies enacted the unified text C. 2-A and abb., which codified provisions on “medically assisted voluntary death” regulating the right to request medical assistance in dying, provided that specific requirements and conditions be met. This short report is meant as an attempt to put into perspective such fundamental values, against the backdrop of the therapeutic alliance between doctors and patients and the ethical, legislative, and regulatory complexities which are bound to arise.